2015
DOI: 10.1016/j.jcp.2014.09.018
|View full text |Cite
|
Sign up to set email alerts
|

An Embedded Split-Step method for solving the nonlinear Schrödinger equation in optics

Abstract: In optics the nonlinear Schrödinger equation (NLSE) which modelizes wave propagation in an optical fiber is mostly solved by the Symmetric Split-Step method. The practical efficiency of the Symmetric Split-Step method is highly dependent on the computational grid points distribution along the fiber, therefore an efficient adaptive step-size control strategy is mandatory. The most common approach for step-size control is the "step-doubling" approach. It provides an estimation of the local error for an extra com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…Per propagation slice the operators are applied in an iterative fashion. However, the operators do not commute and a Strang symmetrisation scheme must be implemented to reduce this error [9]. The symmetrisation relies on how fast operators vary with the propagation coordinate.…”
Section: Defining the Split Step Operators And Split Step Methods For...mentioning
confidence: 99%
“…Per propagation slice the operators are applied in an iterative fashion. However, the operators do not commute and a Strang symmetrisation scheme must be implemented to reduce this error [9]. The symmetrisation relies on how fast operators vary with the propagation coordinate.…”
Section: Defining the Split Step Operators And Split Step Methods For...mentioning
confidence: 99%
“…We have shown that when solving the NLSE (where the nonlinear problem (8) admits an explicit solution), the Step-Doubling method (also referred as the Local Error method [25]) is the method of choice for adaptive step-size control. One alternative approach would be to use an Embedded Split-Step (ESS) scheme, see [4] for a presentation of the ESS method applied to the NLSE and a comparison of the 2 methods. We have also highlighted the difficulty in designing an adaptive step-size control strategy for solving the GNLSE by the S3F method.…”
Section: Resultsmentioning
confidence: 99%
“…N = N 0 as defined in (6)) the nonlinear ODE problem (8) admits an analytical solution and the local error in the S3F method only amounts to the splitting error as given by (10). In such a case, although an approach similar to the one performed to estimate the local error when solving a nonlinear ODE by an ERK method could be considered (involving 2 embedded Split-Step schemes of different orders [4,17]), the usual method for estimating the splitting local error is based on the step-doubling technique. Actually, it is the adaptive step-size control used in conjunction with the S3F method for solving the NLSE presented in [25].…”
Section: Split-step Local Error Estimation By Step-doublingmentioning
confidence: 99%
“…The Split-Step Fourier Method has been extensively explored in one dimensional systems such as the one-dimensional cubic Non-Linear Schrodinger Equation (NLSE) that models the substantive spectral broadening of light (accordingly named supercontinuum generation) as it propagates in fiber. Past studies focused primarily on estimating step-size dependent error and deriving adaptive step-size algorithms for the implementation of the method [12][13][14]. Other studies explored the stability of the method [15] or its application around certain bound solutions of a NLSE such as soliton formation [16].…”
Section: Niche Of the New General Split-step Methodsmentioning
confidence: 99%